Spectrum of Spondyloarthritis Among Chinese Populations - Zhang, Shangzhu; Peng, Linyi; Li, Qingyang; Zhao, Jinwei; Xu, Dong; Zhao, Jiuliang; Wang, Qian; Li, Mengtao; Zhang, Wen; Tian, Xinping; Su, Jinmei; Zeng, Xiaofeng (Current rheumatology reports, 2022)
Purpose of Review This review aims to emphasize interesting and important new findings with a focus on the spectrum of spondyloarthritis (SpA) in China. Recent Findings Over the past decade, significant advances have been made in the investigation of SpA epidemiology, the exploration of genetic and environmental risk factors, the identification of clinical features, and the updating of treatment protocols in the Chinese population. The prevalence of ankylosing spondylitis (AS) in China is 0.20–0.42%, and the prevalence of HLA-B27 in AS patients is 88.8–89.4%. HLA-B*2704 is the most common subtype in Chinese AS patients, followed by HLA-B*2705. HLA-A*01, more precisely HLA-A*01:01, may be associated with psoriatic arthritis (PsA). Tumor necrosis factor inhibitors and IL-17A inhibitors have been shown to be effective and safe for AS patients in China. Juvenile-onset AS is relatively rare, accounting for only 9.1% of the AS population. The prevalence of arthritis related to inflammatory bowel disease is 6.9 to 7.2%. A Chinese study showed that the most frequently prescribed medication was methotrexate (66.4%). Biological agents were prescribed in only16.4% of patients with PsA. Summary This review summarizes the latest research in the epidemiology, pathogenesis, clinical manifestations, and management of SpA among Chinese populations. Multiple HLA associations with SpA have also been described, and it is hoped that discoveries of such ethnic-specific risk factor(s) and understanding of their pathological mechanisms may potentially lead to newer targeted therapies for the Chinese populations worldwide.